Protocol for a randomized controlled trial to test the acceptability and adherence to 6-months of walnut supplementation in Chinese adults at high risk of cardiovascular disease. - Liu, Yishu.; Li, Nan.; Yan, Ni.; Pan, Xiong-fei.; Li, Qiang.; Micha, Renata.; Mozaffarian, Dariush.; Huffman, Mark D.; Wang, Yanfang.; Neal, Bruce.; Tian, Maoyi.; Zhao, Yi.; Wu, Jason H. (Tufts University. Tisch Library., 2021)
Keywords: Nuts, Cardiovascular disease, Randomized controlled trial, Plasma ALA.; Springer Open.